FRESH GRADUATE UROLOGIST IN EASTERN INDONESIA: FIRST YEAR SURGERY EXPERIENCE - Goller, Ardito Ario Willy; Telussa, Arley Sadra (Indonesian Journal of Urology, 2021)
Objective: In present days, endourology is the hallmark of urology, including in developing countries. This study reviews the surgical experiences of a urology practitioner in the first year of his practice in the underdeveloped province in Indonesia. Material & Methods: This research is a descriptive study that retrieval patients data from the medical record during June 2018 - May 2019. Results: Total of 401 operations were obtained. There were 328 male (81.8%) and 73 female (18.2%) with the average of patients age were 52+17.77 years old. The most common diagnoses were BPH 113 cases (28.2%). bladder stone 83 cases (20.7%), and ureteral stone 52 cases (13%). The most common surgical procedures performed were TURP 120 operations (29.9%), Ureterorenoscopy (URS) 64 operations (16%), and Vesicolithotripsy 58 operations (14.5%). The upper tract procedures were 84 operations (20.9%), mainly URS 64 operations (16%). Whereas the lower procedures were 317 operations (79.1%) mainly TURP 120 operations (29.9%). The complications were bleeding post-TURP 5 cases which require blood clot evacuation (1.2%), bleeding post open nephrolithotomy 1 case which requires blood transfusion (0.2%), and TURP syndrome 1 case (0.2%) with mortality 2 patient (0.4%). All kidney stones were handled by open surgery due to lack of PCNL and ESWL set devices. Conclusion: First year urologist who are interested in serving in such areas may benefit from prioritizing the availability of upper and lower set to performed basic standard care for surgical urology without leaving the hallmark of urology.